The Cytotoxic Effects of Moringa oleifera Leaf Extract and Silver Nanoparticles on Human Kasumi-1 Cells - Khor KZ (Dove Medical Press, 2020)
Kang Zi Khor,1 Julia Joseph,1 Farah Shamsuddin,1 Vuanghao Lim,1 Emmanuel J Moses,2 Nozlena Abdul Samad1 1Integrative Medicine Cluster, Advance Medical and Dental Institute (AMDI), University Sains Malaysia, Penang, Malaysia; 2Regenerative Medicine Cluster, Advance Medical and Dental Institute (AMDI), University Sains Malaysia, Penang, MalaysiaCorrespondence: Nozlena Abdul SamadIntegrative Medicine Cluster, Advance Medical and Dental Institute, University Sains Malaysia, Jalan Bertam 2, Mukim 6, 13200, Kepala Batas, Penang, MalaysiaTel +604 - 562 2051Fax +604 - 562 2349Email nozlena@usm.myBackground: Moringa oleifera, commonly known as “moringa”, is widely cultivated in tropical and subtropical regions across the globe. Extensive studies have shown that various parts of the moringa tree exhibit anti-cancer properties. This study determined the effects of sequential moringa leaf extracts and silver nanoparticles synthesized from moringa leaf extract on Kasumi-1 leukemia cells.Methods and Results: Dried moringa leaf powder was sequentially extracted with the assistance of ultrasound starting with absolute ethanol, followed by 50% ethanol, and finally, deionized water. The aqueous extract was utilized to synthesize silver nanoparticles. The optimum conditions to generate moringa silver nanoparticles (MO-AgNPs) were eight hours of incubation at 60°C with 1 mM silver nitrate and 1% moringa aqueous extract from sequential extraction. The three extracts and MO-AgNPs were used to treat Kasumi-1 cells for 24, 48, 72 hours with concentrations ranging from 400 to 12.5 μg/mL, while cell viability was determined with 3(4, 5-dimethythiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. After 72 hours of treatment, the moringa leaf absolute ethanol extract displayed the strongest inhibitory effects on Kasumi-1 cells with IC50 of 10 μg/mL, in comparison to moringa leaf 50% ethanol extract (25 μg/mL) and aqueous extract (> 400 μg/mL). Interestingly, MO-AgNPs exhibited the strongest cytotoxic effects on Kasumi-1 cells with an IC50 of 7.5 μg/mL. Cytotoxic study on normal CD34+ cells treated with up to 50ug/mL of either MO-AgNPs or ethanol extract still had more than 80% cell viability indicating that the treatments have selective cytotoxicity against the cancer cells. Morphological studies of Kasumi-1 cells treated with IC50 of moringa leaf ethanolic extract and MO-AgNPs show a lot of shrinking, dying cells and cell debris. Cell cycle studies displayed an increase in cells at the G1 phase for ethanol leaf extract, while MO-AgNPs caused cell cycle arrest at the S phase after treatment with IC50 dose for 24 hours. Moringa leaf ethanol extract and the nanoparticles induced apoptosis in Kasumi-1 cells as shown by annexin V – FITC assays. Gene expression analysis by qPCR verified these outcomes, as the moringa leaf ethanol extract led to significant upregulation of proapoptotic gene caspase 8, whereas the MO-AgNPs caused a significant increase of proapoptotic protein BID.Conclusion: This study reveals that moringa ethanolic leaf extract and MO-AgNPs induced potent antiproliferative effects in Kasumi-1 cells by apoptosis.Keywords: ultrasound, sequential extraction, green synthesis, silver nanoparticles, leukemia